Perkembangan Nilai-Nilai Pendidikan Karakter Pada Mahasiswa Sejarah di Era New Normal - Agus Susilo; Dodik Mulyono (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
Character education is education that is related to the character, values, and norms that apply in society. This study aims to determine the development of character education values in history students in the new normal era. Character education in the New Normal is a problem that must be known as the material for this research. The method in this research is descriptive qualitative study. The sources in this study are the results of observations of researchers in the field which were developed with other sources such as interviews, sources of books and relevant research journals to be studied. The results and discussion of this research is that education in New Normal Era Universities is in the pandemic era and the New Normal era due to the Covid-19 pandemic, Universities are experiencing the impact of this. Universities must begin to adjust to the new conditions that occur in Indonesia. Even though it has entered the New Normal era, universities still have to be disciplined in maintaining the process that the government wants. This is very important to save the Indonesian people so that the Covid-19 pandemic outbreak can be resolved properly. While character education in the New Normal era is the condition of History students during learning activities during the New Normal era. The behavior caused by History students during online and face-to-face learning is limited to being studied to determine the level of character that is the subject of research. Basically, the problems that arise during learning in the New Normal era are related to the formation of the attitude of History students to remain conducive during the New Normal era.